Increased Circulating Levels of CRP and IL-6 and Decreased Frequencies of T and B Lymphocyte Subsets Are Associated With Immune-Related Adverse Events During Combination Therapy With PD-1 Inhibitors for Liver Cancer - Yu, Yingying; Wang, Siyu; Su, Nan; Pan, Shida; Tu, Bo; Zhao, Jinfang; Shen, Yingjuan; Qiu, Qin; Liu, Xiaomeng; Luan, Junqing; Wang, Fu-Sheng; Meng, Fanping; et al. (Frontiers in Oncology, 2022)
Background: Programmed cell death protein 1/programmed death-ligand 1 (PD-1/PD-L1) immune-related adverse events (irAEs) are inevitable in patients with liver cancer. Although the incidence of severe irAEs is low, but can result in fatal consequences. To date, only a few commonly used clinical biomarkers have been reported. Aim: To assess commonly used clinical biomarkers associated with the occurrence of irAEs to enable better management of irAEs by clinicians. Methods: We retrospectively reviewed patients with liver cancer treated with at least one cycle of PD-1 immune checkpoint inhibitors (ICIs) combined with tyrosine kinase inhibitors (TKIs). IrAEs were documented according to the common terminology criteria for adverse events version 5. Clinical and laboratory parameters were also evaluated. Results: A total of 67 patients were included, 36 with irAEs and 31 without irAEs. A total of 104 adverse events occurred; 83 of these events were grade 1/2 (G1/G2), 21 were grade 3/4 (G3/G4), and one died of G4 hepatitis. Patients with irAEs had higher levels of C-reactive protein (CRP) and interleukin-6 (IL-6) and lower levels of lymphocyte subsets, except natural killer (NK) cell counts, than those without irAEs (P <0.05). Patients who experienced G3/G4 irAEs had higher levels of CRP and IL-6 and lower levels of CD4+ T lymphocytes and B lymphocytes than those who experienced G1/G2 irAEs (P <0.05). Of note, impairments in liver function and routine blood tests were also observed (P <0.05). The results of univariate and multivariate analyses for any grade of irAEs revealed that the combination of sintilimab and lenvatinib (P= 0.004, odds ratio [OR]: 7.414, 95% confidence interval [95% CI]: 1.925–28.560) and CRP ≥8.2 mg/L (P= 0.024, OR: 3.727, CI: 1.185–11.726) were independent risk factors. Univariate and multivariate analyses of the risk factors of G3/G4 irAEs suggested that the combination of sintilimab and lenvatinib was a potential risk factor (P = 0.049, OR: 8.242, CI: 1.006–67.532). Conclusion: Changes in patient CRP, IL-6, and lymphocyte subsets were associated with irAE onset and may act as potential biomarkers of irAEs. Impairments in liver function and routine blood tests owing to the occurrence of irAEs may become new concerns for clinicians.